2009
DOI: 10.4111/kju.2009.50.7.669
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy: A Single Center Experience of 610 Cases

Abstract: Purpose: We performed this study to evaluate the outcomes and complications of percutaneous nephrolithotomy (PCNL) at a single institute with a large series. Materials and Methods:We reviewed the medical records of 610 patients who underwent PCNL between March 1995 and June 2008 for staghorn calculi in 139 (22.8%), partial staghorn calculi in 104 (17.0%), renal pelvis stone in 222 (36.4%), proximal ureter calculi in 60 (9.8%), and calculi within a caliceal diverticulum in 85 (13.9%) patients. Stone-free status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The most recent Korean report of PCNL performed in single large center was published in 2009 by Kwon et al [ 13 ]. In their retrospective report comprising 610 patients, the initial stone-free rate was 57.6% and the overall stone-free rate was 84.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent Korean report of PCNL performed in single large center was published in 2009 by Kwon et al [ 13 ]. In their retrospective report comprising 610 patients, the initial stone-free rate was 57.6% and the overall stone-free rate was 84.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to a large-scale study, initial and overall stone-free rates were 69.9% and 88.8%, respectively [ 27 ], and another study conducted on 610 patients found corresponding rates of 57.6% and 84.9%, respectively [ 28 ]. In the present study, values were 68.8% and 80.5% in the regional anesthesia group and 42.9% and 71.4% in the general anesthesia group, which were relatively low and did not represent a significant intergroup difference.…”
Section: Discussionmentioning
confidence: 99%